2012
DOI: 10.1007/s10562-012-0798-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pd/SiO2 Nanobeads for Use in Suzuki Coupling Reactions by Reverse Micelle Sol–gel Process

Abstract: Pd/SiO 2 nanobeads containing tiny Pd clusters with a diameter of about 2 nm were prepared via a sol-gel process for SiO 2 by using a water-in-oil microemulsion with Pd complexes and subsequent hydrogen reduction by heat treatment. The Pd/SiO 2 nanostructures were employed in Suzuki coupling reactions with various substrates, and they served as good catalysts in these reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…[4][5][6][7][8] With regards to supporting Pd complexes on solid carriers, the catalysts could be recycled, but they give worse performances after each cycle, which is mainly due to the aggregation of Pd. 9,10 The third choice is supported Pd nanoparticle catalysts; however, they do not have enough activity under mild conditions for their determined, dynamic structures. [11][12][13][14][15][16][17][18][19][20] Inspiringly, heterogeneous single-atom catalyst emerged as the most potential candidate to settle these challenges, precisely, by providing a bridge between heterogeneous and homogeneous catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] With regards to supporting Pd complexes on solid carriers, the catalysts could be recycled, but they give worse performances after each cycle, which is mainly due to the aggregation of Pd. 9,10 The third choice is supported Pd nanoparticle catalysts; however, they do not have enough activity under mild conditions for their determined, dynamic structures. [11][12][13][14][15][16][17][18][19][20] Inspiringly, heterogeneous single-atom catalyst emerged as the most potential candidate to settle these challenges, precisely, by providing a bridge between heterogeneous and homogeneous catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it was observed that hybrid Augraphene oxide (GO) nanosheets, dumbbell-and flower-like Au-Fe 3 O 4 heterostructures, and trimetallic Au@PdPt core-shell nanoparticles exhibited excellent catalytic activity in the reduction of nitro compounds [15][16][17] . Our efforts have focused on developing Pd hybrid nanoparticles with bifunctional structures that contain active Pd nanoparticles embedded on metal oxide supports or carbonbased materials and on verifying the influence of porosity and organic capping agents on the effective catalytic activity of these nanoparticles in the Suzuki coupling reaction [21][22][23][24][25][26] . In a recent work in our laboratory, hybrid nanoparticles with various structures and chemical compositions were successfully developed and utilized as catalysts for organic reactions such as azide-alkyne cycloaddition reactions, reduction of nitroarenes, and propargylation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The Suzuki‐Miyaura coupling reaction, which creates new carbon‐carbon bonds between organohalides and boronic acid derivatives, has been utilized for the production of fine chemicals, polymers, and pharmaceutical products, using palladium (Pd)‐based catalysts in alkaline condition . Typically, heterogeneous Pd nanocatalysts such as Pd nanoparticles (NPs), Pd/C, Pd/SiO 2 , and Pd/Al 2 O 3 have been applied to the reaction . Recently, an ordered mesoporous carbon (CMK‐3) with high surface areas, pore volumes, and uniform pore sizes has been introduced as a catalyst support, providing good reactant diffusion surroundings and enhanced durability for the active sites ,…”
Section: Methodsmentioning
confidence: 99%